Potential for the use of macrolides in the antimicrobial therapy of severe community-acquired pneumonia in adults - Sinopalnikov A.I. (Клиническая микробиология и антимикробная химиотерапия, 2019)
This paper presents mechanism of action and antimicrobial spectrum of macrolides as well as the known acquired resistance mechanisms in the common pathogens causing community-acquired pneumonia, such as Streptococcus pneumoniae and Mycoplasma pneumoniae. Non-antimicrobial (anti-inflammatory and immunomodulatory) effects of macrolides that have been found in experimental and clinical studies are described in detail. Results of clinical studies and current practice guidelines which determine potential benefits and a role of macrolides in the antibacterial therapy of severe community-acquired pneumonia in adults are reviewed.